A Causal Model of Parenting Stress Based on Child Behavioral Problems, Parental Perfectionism, Psychological Inflexibility, and Family Conflict: The Mediating Role of Parental Self-Compassion - Mori, Keisuke; Holloway, Ethan; Lundqvist, Erik (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to develop and test a causal model of parenting stress based on child behavioral problems, parental perfectionism, psychological inflexibility, and family conflict, with parental self-compassion serving as a mediating variable among Canadian parents. Methods and Materials: This study employed a cross-sectional correlational design using structural equation modeling (SEM). The statistical population consisted of Canadian parents with at least one child aged 6–16 years. Using purposive sampling, 620 parents were recruited from schools, community family centers, parenting organizations, and online parenting networks across several Canadian provinces. Data were collected using the Parenting Stress Index–Short Form (PSI-SF), Strengths and Difficulties Questionnaire (SDQ), Multidimensional Perfectionism Scale (MPS), Acceptance and Action Questionnaire-II (AAQ-II), Family Environment Scale (FES–Conflict Subscale), and Self-Compassion Scale (SCS). Data were analyzed using SPSS version 27 and AMOS version 24. Descriptive statistics, Pearson correlation coefficients, confirmatory factor analysis, and structural equation modeling were conducted. The mediating role of parental self-compassion was examined using bootstrap analysis with 5,000 resamples and 95% bias-corrected confidence intervals. Findings: The proposed structural model demonstrated satisfactory fit to the data (χ²/df = 2.58, CFI = .95, TLI = .95, IFI = .95, GFI = .92, RMSEA = .051). Child behavioral problems (β = .24, p < .001), parental perfectionism (β = .17, p < .001), psychological inflexibility (β = .31, p < .001), and family conflict (β = .22, p < .001) had significant positive direct effects on parenting stress. Child behavioral problems (β = -.16, p < .001), parental perfectionism (β = -.23, p < .001), psychological inflexibility (β = -.41, p < .001), and family conflict (β = -.19, p < .001) significantly predicted lower parental self-compassion. Parental self-compassion had a significant negative effect on parenting stress (β = -.46, p < .001). Bootstrap analyses confirmed significant indirect effects of all predictor variables on parenting stress through parental self-compassion (p < .001). The model explained 68% of the variance in parenting stress and 57% of the variance in parental self-compassion. Conclusion: The findings indicate that parenting stress is influenced by a complex interplay of child-related, parent-related, and family-system factors. Child behavioral problems, parental perfectionism, psychological inflexibility, and family conflict increase parenting stress both directly and indirectly through reductions in parental self-compassion. Among the predictors, psychological inflexibility emerged as the strongest risk factor, whereas parental self-compassion functioned as a significant protective mechanism. These results highlight the importance of interventions targeting self-compassion, psychological flexibility, and family relationship quality to reduce parenting stress and promote parental well-being.